Structure-based design and synthesis of a novel long-chain 4′′-alkyl ether derivative of EGCG as potent EGFR inhibitor: in vitro and in silico studies. Issue 28 (16th June 2022) - Singh, Satyam; Sahadevan, Revathy; Roy, Rajarshi; Biswas, Mainak; Ghosh, Priya; Kar, Parimal; Sonawane, Avinash; Sadhukhan, Sushabhan
Abstract : Among the synthesized 4′′-alkyl EGCG derivatives, 4′′-C14 EGCG inhibited EGF stimulated phosphorylation of EGFR and its downstream signaling pathways, ERK and Akt. 4′′-C14 EGCG showed significantly improved stability than EGCG and induced apoptosis. Abstract : Herein, we report the discovery of a novel long-chain ether derivative of (−)-epigallocatechin-3-gallate (EGCG), a major green tea polyphenol as a potent EGFR inhibitor. A series of 4′′-alkyl EGCG derivatives have been synthesized via regio-selectively alkylating the 4′′ hydroxyl group in the D-ring of EGCG and tested for their antiproliferative activities against high (A431), moderate (HeLa), and low (MCF-7) EGFR-expressing cancer cell lines. The most potent compound, 4′′-C14 EGCG showed the lowest IC50 values across all the tested cell lines. 4′′-C14 EGCG was also found to be significantly more stable than EGCG under physiological conditions (PBS at pH 7.4). Further western blot analysis and imaging data revealed that 4′′-C14 EGCG induced cell death in A431 cells with shrunken nuclei, nuclear fragmentation, membrane blebbing, and increased population of apoptotic cells where BAX upregulation and BCLXL downregulation were observed. In addition, autophosphorylation of EGFR and its downstream signalling proteins Akt and ERK were markedly inhibited by 4′′-C14 EGCG. MD simulation and the MM/PBSA analysis disclosed the binding mode of 4′′-C14 EGCG in the ATP-binding site of EGFR kinase domain. Taken together, our findings demonstrate that 4′′-C14 EGCG can act as a promising potent EGFR inhibitor with enhanced stability.